Spontaneous flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv). 3. Escaped plants - O. Shynder (Інтродукція Рослин, 2019)
Objective – to study the species composition and structure of spontaneous flora in M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv).